(untitled) (Mongolian Journal of Chemistry, 2024)
The coordination complexes of Mn(II), Co(II), Ni(II), Cu(II) Zn(II) and VO(II) derived from novel azo-Schiff base ligand 2-((E)-(5-bromo-2-hydroxy-3-((E)-((3-hydroxypyridin-2-yl)imino)methyl)phenyl)diazenyl)pyridin-3-ol using (E)-5-bromo-2-hydroxy-3-((3-hydroxy-pyridin-2-yl)diazenyl)benzaldehyde with 2-amino-3-hydroxy pyridine. These are characterized by FT-IR spectra, 1H-NMR spectra, mass spectra, electronic spectra, elemental analysis, thermal analysis, X-ray powder diffraction, molar conductivity etc. In biological studies, the synthesized ligand and its metal complexes were screened for antimicrobial activity against two-gram positive bacteria, two-gram negative bacteria and three fungi. The Neuroprotective activity was tested against SHSY-5Y Neuroblastoma cell line by MTT assay. The anticancer activity was screened against the human MCF-7 breast cancer cell line by using Sulfo-Rhodamine-B-stain (SRB) assay. The observations suggest that metal complexes exhibited good activities than ligand.